Ice: a challenge to the engineer - Gold, L. W. (1973)
Forces due to ice are a major problem for the design of hydraulic structures and ice breakers, particularly with respect to development activity in the Arctic. The paper presents a review of the characteristics of the structure of natural ice, the deformation behaviour of single crystals, and the deformation and strength behaviour of polycrystalline ice. Particular attention is given to recent work on crack formation and failure. Current ice engineering problems and the work being carried out on them are described. Les forces dues à la glace posent un problème majeur à la réalisation de constructions hydrauliques et à la création de brise-glace, surtout en ce qui concerne le développement de l'Arctique. L'auteur passe en revue les caractéristiques structurales de la glace naturelle, la déformation de cristaux individuels, ainsi que la déformation et la résistance de la glace polycristalline. On accorde une attention particulière aux travaux récents sur la formation de fissures et la rupture. L'auteur décrit les problèmes techniques que pose présentement la glace et l'étude qu'on en fait. Peer reviewed: No NRC publication: Yes